Towards Enterprise-Oriented Software Development Environments - Villela, Karina; Travassos, Guilherme Horta; Rocha, Ana Regina Cavalcanti da (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
Software developers need to make intensive use of knowledge throughout the software development process. There are different kinds of relevant knowledge in this context, such as domain knowledge, organizational guidelines, best practices, software techniques and methods, prior experiences using these techniques, methods and the software process. This knowledge is accumulated by the company’s staff and can be useful in supporting software projects and organizational learning on software development. However, knowledge identification, organization, storage and usage are not trivial. To support the usage of such knowledge during software development we propose a new family of software development environments: the Enterprise-Oriented Software Development Environments (EOSDE). The EOSDE approach is based on both Knowledge Management (KM) and Experience Factory (EF) concepts. EOSDE are intended to support two types of Companies: Software Companies, in which the business activity is to develop software solutions for several clients, and Non-Software Companies, in which the software development activity aims at supporting the business activity.